IMPLEMENTASI TERAPI AIUEO DENGAN GANGGUAN AFASIA MOTORIK PADA PASIEN STROKE DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Tajri Arrizqa Br Barus; Erita Gustina; Huwaina Af’idah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Stroke is a clinical syndrome characterized by focal or global cerebral dysfunction lasting for 24 hours or more, which may lead to disability or death and is caused by spontaneous bleeding or inadequate blood supply to brain tissue. Motor aphasia is a condition involving damage to the entire cortex in the Broca's area. Motor aphasia manifests as verbal impairment accompanied by symptoms such as difficulty speaking, dysarthria, and visible increased effort when attempting to communicate. The AIUEO therapy is a treatment designed to improve speech so that it can be better understood by others by moving the tongue, lips, facial muscles, and pronouncing the sounds